VD_FINDINFO Jug / 2013 / 302 vom 5. Juni 2013 - VD Tribunal cantonal (2013)
PORNOGRAPHIE, SURSIS À L'EXÉCUTION DE LA PEINE, DIRECTIVEINJONCTION | 106 CP, 197 ch. 1 CP, 197 ch. 3 CP, 40 CP, 42 CP, 44 CP, 47 CP